1983
DOI: 10.1016/s0022-5347(17)52482-9
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the Female Urethra: Reassessment of Modes of Therapy

Abstract: Of 15 women with primary urethral carcinoma 2 had tumors confined to the urethra and were managed successfully by an operation. Of the 9 patients with tumor extending to the surrounding structures 6 (67 per cent) died of complications related to inadequate control of the primary tumor. The last 4 patients had stage D1 disease or greater at initial diagnosis and died of distant metastases. Our current approach for patients with locally advanced disease is combined brachytherapy and operation in an effort to era… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…After reviewing the titles, abstracts and full texts, we selected 92 studies for qualitative synthesis (Fig. 1) [1,2,4–6,8–95].…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the titles, abstracts and full texts, we selected 92 studies for qualitative synthesis (Fig. 1) [1,2,4–6,8–95].…”
Section: Resultsmentioning
confidence: 99%
“…Hopkins et al [14] reported on 15 patients with malignant urethral neoplasms. 13 % of the patients had low stage disease (A or B) and did well with surgical treatment alone, while 27 % of the patients had advanced disease (D 1 or greater) and died rapidly of metastases.…”
Section: Discussionmentioning
confidence: 99%
“…13 % of the patients had low stage disease (A or B) and did well with surgical treatment alone, while 27 % of the patients had advanced disease (D 1 or greater) and died rapidly of metastases. Of the 9 patients in the group with local extention of their disease (stage C), 67% died, most often from inadequate control of local disease [14]. Good results, especially with lower stage dis ease is obtained with combined therapy; usually irradia tion of the tumor site followed by radical surgery [12], Squamous cell carcinoma is the most common ure thral tumor and usually involves the distal or entire ure thra [8].…”
Section: Discussionmentioning
confidence: 99%